EFEKTIFITAS SENAM AEROBIC LOW IMPACT TERHADAP PENURUNAN SKOR HALUSINASI - R Dwi Safra Yuli; Jumaini ' '; Yesi ' Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to determine effectiveness of low impact aerobic exercise toward decrease score of hallucination. The method of this research was quasy experiment with pretest-posttest design with control group. The research was conducted in psychiatric hospital Tampan Riau Province with sample of 32 patients with risk of violence behaviour which divided into 15 people as experimental group and 17 people as control group and the sampling method was purposive sampling. Instruments of this research used score hallucinasion questionnaire which has tested the validity and reliability. Experimental group was given low impact aerobic exercise for three times a week for 2 weeks, meanwhile control group were not. The analysis that used in this research were univariate and bivariate analysis used wilcoxon test and mann-whitney. The result of the research showed that there was significant decrease score of hallucination after given intervention low impact aerobic exercise between experimental group with p value 0,01 (p < 0,05), in conclusion low impact aerobic exercise is effective toward decrease score of hallucination. The result of this research recommended to be applied for nursing intervention to patient’s hallucination. Keywords : Hallucination, low impact aerobic exercise, score of hallucination. Reference : 76 (2000-2014)